Orientation and Training of Human Resources in Sports Organizations - Fatkhul Imron; Teguh Santosa; Risa Agus Teguh Wibowo; Kodrad Budiyono; Dina Yuli Puspita; Nida Padang Haura; Bintang Qori Az Zahra (International Journal of Asian Business and Management, 2024)
In the process, sports human resource management is closely related to procurement, training, evaluation, compensation, work relations, health, security and justice for individuals in an organization. Human resources in the field of sports play a very important role in the management of sports organizations to manage and create effective, efficient and systematic performance that supports the needs of sports people and creates conditions that enable these human resources to make optimal contributions to sports organizations. To create human resources in the field of sports that are superior in intellectual, moral, spiritual, competitiveness and professionalism aspects, good human resource management capabilities are needed through training and application of operational principles and functions. Orientation and training are very important in the organization's operational processes to develop human resource capabilities in the sports sector